Russia’s tactics in suppressing Ukraine’s sovereignty - Kruszczynski, Madeline S. (Young Scholars Grinchenko – Seton International Journal, 2025)
Ukraine has long struggled to assert its sovereignty, from World War I to the Holodomor famine under Stalin, and now in its ongoing battle for independence amidst the Russia-Ukraine war, which escalated in February 2022 following Russia’s full-scale invasion of Ukraine. Whether through forced starvation or disinformation campaigns, Ukraine has repeatedly been tested, yet it continues to stand resilient. As technology has advanced, so too have Russia’s methods for suppressing Ukraine’s independence. This paper argues that Russia’s suppression of Ukrainian sovereignty has evolved from physical oppression to digital warfare, marking a continuous and adaptive campaign that not only challenges Ukraine’s independence but also the foundations of modern democratic statehood.